Edge Computing and its Synergy with Cloud Computing: An Overview - Goutham Sabbani (North American Journal of Engineering Research, 2024)
Real-time data processing has changed a lot with the adoption of edge computing. For example, smart cities like Singapore and Barcelona reduced their traffic congestion by 40% through local data analysis. This technology transformed the gap between cloud services and end devices [1].We will explore the synergy between edge and cloud computing. We are highlighting their complementary roles in enhancing data processing efficiency and scalability. We discuss the evolution of cloud computing, its integration with cloud infrastructure, and the resulting benefits in various applications. The paper will delve into crucial advances such as data latency reduction bandwidth optimization, including security concerns, deployment complexities, and the role of AI in optimizing edge operations and improving user experience. Additionally, we will examine challenges and prospects, providing a comprehensive understanding of how edge computing works alongside cloud computing to meet modern technological demands